PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PADA PT RAMAI TEKNOLOGI INDONESIA DI KABUPATEN TANGERANG - Alinda Alinda; Heru Sudinta; Temmy Setiawan (MANTRA (Jurnal Manajemen Strategis), 2026)
The Influence of Transformational Leadership Style and Work Motivation on Employee Performance at PT Ramai Teknologi Indonesia in Tangerang Regency. This study examines the partial and simultaneous effects of transformational leadership style and work motivation on employee performance. Using a quantitative survey of 30 employees, the results show that both variables have positive and significant effects on employee performance.